Students’ Perception on the Use of Pedagogical Translation in Learning English at Poltekkes Kemenkes Padang. - Nahampun, Nony Ramadhani; Oktavia, Witri (Journal of English Language Teaching, 2025)
English language proficiency is one of the important competencies that have to be possessed by the students at Poltekkes Kemenkes Padang. As a health education institution, English language skills can support students in accessing information, communicating, and expanding their horizons in the health sector. One approach that can be used to help students learn English is by using pedagogical translation. Pedagogical translation refers to the use of translation as a tool in the English learning process. This study aimed to find the students’ perception on the use of pedagogical translation in learning English at Poltekkes Kemenkes Padang. The method used in this study was descriptive research that used closed-ended questionnaire and structured written interview to collect the data. The participants of this study were 40 students of Poltekkes Kemenkes Padang. The findings showed that mostly the students have positive perception that the using of pedagogical translation provides many benefits related to the students’ language proficiency, such as, remembering and discovering new English vocabulary, improving their understanding in learning English, and making a progress in learning English.